Agility Training For Futsal Players: A Systematic Literature Review (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Purpose: The purpose of this study was to determine the benefits of agility training in Futsal players. Materials and Methods: The PRISMA table will be used for systematic review and meta-analysis in this review investigation. Various studies were published from January 2020 to December 2025. In the search procedure, the following keywords were used: (1) Training; (2) Agility; (3) Futsal. The search in this study utilized the Scopus research journal database. Results: The theme of this study as a whole obtained 42. Consists of 23 articles which are then taken 10 relevant. Conclusion: The analysis of agility training in futsal players, based on the results of relevant research, reveals significant improvements in agility, movement reactions, and physical performance. However, further research is needed to adjust the training to the specific characteristics of athletes.